WORD-FORMATION - Abdullayeva Nazokatxon To’lqin qizi; Saminova Mashhura Rafiqjon qizi; Ahmedova Matlubaxon Ibragimjonovna (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Anotation: Word formation refers to the processes by which new words are created in a language. There are several methods and features of word formation that contribute to the expansion and evolution of a language The study of word formation is one method to improve the vocabulary in English. The average speaker typically takes the rules governing the creation of new words and their adoption nto the language for granted. This article explores these rules